Obtaining a Fire-Resistant Coating Based on Acrylonitrile and Phosphoric Acid - Tojidinov Mashhurbek Baxodirovich (Genius Journals, 2022)
Increasing the fire resistance of wooden structures is an important task that must be solved for their long and safe operation. When a wooden structure catches fire, it can collapse and burn completely in 20-30 minutes. Fire retardants allow you to slow down the burning process by 2-3 times and prevent serious consequences. During this time, necessary measures can be taken, people can be taken out, valuables can be saved.
Keywords: Acrylonitrile; phosphoric acid; fire-resistant